2023
DOI: 10.1101/2023.12.12.571219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional divergence shaped the network architecture of plant immune receptors

Ching-Yi Huang,
Yu-Seng Huang,
Yu Sugihara
et al.

Abstract: In solanaceous plants, several sensor NLRs and their helper NLRs, known as NRC, form a complex network to confer immunity against pathogens. While the sensor NLRs and downstream NRC helpers display diverse genetic compatibility, the evolution and molecular basis of the complex network structure remained elusive. Here we demonstrated that functional divergence of NRC3 variants has shaped the genetic architecture of the NLR network. Natural NRC3 variants form three allelic groups displaying distinct compatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To date, conclusive evidence that NRC-dependent sensors and their NRC helpers form stable complexes has not been obtained. This is largely due to sensor-helper co-immunoprecipitation studies being notoriously difficult to control properly, as was shown recently by Huang et al in their recent study (Huang et al, 2023). In this same study, however, Huang et al leveraged Turbo-ID to reveal that NRC-dependent sensors specifically show enhanced interactions with their corresponding downstream helpers following activation, in support of a model in which NRC activation is mediated by transient sensor-helper interactions.…”
Section: Discussionmentioning
confidence: 63%
“…To date, conclusive evidence that NRC-dependent sensors and their NRC helpers form stable complexes has not been obtained. This is largely due to sensor-helper co-immunoprecipitation studies being notoriously difficult to control properly, as was shown recently by Huang et al in their recent study (Huang et al, 2023). In this same study, however, Huang et al leveraged Turbo-ID to reveal that NRC-dependent sensors specifically show enhanced interactions with their corresponding downstream helpers following activation, in support of a model in which NRC activation is mediated by transient sensor-helper interactions.…”
Section: Discussionmentioning
confidence: 63%
“…Ancestral sequence reconstruction statistically infers intermediate sequences at phylogenetic nodes, enabling the identification of key evolutionary mutations. It is increasingly being applied to plant-pathogen coevolutionary systems (Bentham et al, 2021; Białas et al, 2021; Huang et al, 2023; Schornack and Kamoun, 2023). For instance, this method was used to explore when the rice sensor NLR Pik-1 evolved to detect the AVR-PikD effector of the pathogenic fungus Magnaporthe oryzae (syn.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ancestral sequence reconstruction was applied to the AVR-Pik effector family to understand the directionality of evolutionary changes, determining whether the effector family expanded host-target binding or host immunity evaded the effector family (Bentham et al, 2021). Moreover, a recent study employed this technique on NRC3 to examine the evolutionary history of sensor-helper compatibility (Huang et al, 2023). In our study, we applied ancestral sequence reconstruction to NRC3 and reconstructed the coevolutionary dynamics between NLRs and pathogen immunosuppressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations